2016
DOI: 10.1192/pb.bp.114.048496
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Adherence Programme: evaluation of an innovative service model

Abstract: Aims and method The Maintaining Adherence Programme (MAP) is a new model of care for patients with schizophrenia, schizoaffective disorder and bipolar affective disorder which aims to encourage adherence and prevent relapse. This evaluation, conducted by retrospective and prospective data collection (including patient questionnaires and staff interviews), aimed to describe MAP's impact on healthcare resource use, clinical measures and patient and staff satisfaction, following its implementation in a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Comparison of our study with the studies in Germany and England [10, 12] reveals similarities and differences regarding the programmes themselves and their study designs. First, the content of each programme was very similar, focusing on psychoeducation on the psychiatric condition, and also on adherence and preventing rehospitalization.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Comparison of our study with the studies in Germany and England [10, 12] reveals similarities and differences regarding the programmes themselves and their study designs. First, the content of each programme was very similar, focusing on psychoeducation on the psychiatric condition, and also on adherence and preventing rehospitalization.…”
Section: Discussionmentioning
confidence: 73%
“…This German programme was also adopted and implemented in England as the Maintaining Adherence Programme, where, in a pre-post design, it significantly reduced in-patient bed days by 42% in the intention-to-treat analysis and by 51% reduction in the completer analysis [12]. The same study also showed a significant cost reduction and very high patient and staff satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…New practices were described by 20 (28.6%) of the included studies, consisting of disease management programmes (eg, heart failure disease management programme38, maintaining adherence programme for patients with schizophrenia39), introduction of additional assessments (eg, comprehensive geriatric screening in the emergency department40 41) and the use of novel forms (eg, inpatient order set for therapeutic-dose dalteparin,42 Physician Orders for Life-Sustaining Treatment (POLST) form43).…”
Section: Resultsmentioning
confidence: 99%